Expression levels of paraoxonase-1 in aortic valve tissue are associated with the progression of calcific aortic valve stenosis - Song, Jian; Zheng, Qiang; Ma, Xiaochun; Zhang, Qian; Xu, Zhenqiang; Zou, Chengwei; Wang, Zhengjun (Journal of Thoracic Disease, 2019)
Background: Paraoxonase-1 (PON1) participates in several vital steps of lipid metabolism, which is associated with calcific aortic valve stenosis (CAVS). Although a few studies have suggested that PON1 in blood could inhibit aortic valve calcification, they did not provide detailed descriptions. In this study, we hypothesized that PON1 is expressed in the aortic valve and that the PON1 level is related to the severity of CAVS. Methods: A total of 118 consecutive patients with CAVS were enrolled in the study; 35 individuals without aortic valve calcification were included in the control group. Aortic valve tissue was obtained from postoperative pathologic specimens. PON1 was detected qualitatively using immunohistochemistry and quantitatively using an enzyme-linked immunosorbent assay. The severity of aortic stenosis was evaluated using echocardiography. Results: We detected PON1 in the aortic valve and noticed that the PON1 level was significantly lower in the case group than in the control group (P